Description of the larvae of four Japanese Platambus Thomson, 1859 (Coleoptera: Dytiscidae: Agabinae) with phylogenetic considerations - Okada, Ryohei; Alarie, Yves; Michat, Mariano C. (Zootaxa, 2019)
The larvae of four species of Platambus Thomson, 1859 from Japan, P. pictipennis (Sharp, 1873), P. convexus Okada, 2011, P. fimbriatus (Sharp, 1884) and P. sawadai (Kamiya, 1932) are described for the first time including a detailed chaetotaxy analysis of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. A provisional parsimony analysis based on 39 informative larval characteristics of 15 species in seven genera of the subfamily Agabinae was conducted using the program TNT. Larvae of the Platambus species studied stand out from those of other genera of Agabinae by the unique presence of a subquadrate last abdominal segment not protruding posteriorly into siphon and the much shorter length of the primary urogomphal seta UR5 compared to seta UR7 in first instar larva.